Rhizosphere Streptomyces formulas as the biological control agent of phytopathogenic fungi Fusarium oxysporum and plant growth promoter of soybean - MAYA SARI; ABDJAD ASIH NAWANGSIH; Aris Tri Wahyudi (Society for Indonesian Biodiversity, 2021)
Abstract. Sari M, Nawangsih AA, Wahyudi AT. 2021. Rhizosphere Streptomyces formulas as the biological control agent of phytopathogenic fungi Fusarium oxysporum and plant growth promoter of soybean. Biodiversitas 22: 3015-3023. Rhizosphere Streptomyces are considered as promising sources of plant growth-promoting rhizobacteria (PGPR) and biocontrol agents against pathogenic fungi, particularly Fusarium oxysporum causing root rot, cotyledon rot, hypocotyl rot, and stunted growth in soybean. Formulation of rhizosphere Streptomyces with appropriate carrier materials is necessary to facilitate storage and application in plants. This study aimed to develop a formulation of rhizosphere Streptomyces, apply the formula to control F. oxysporum, and promote soybean plant growth. Five Streptomyces isolates, i.e., Streptomyces panaciradicis ARK 13, Streptomyces tritolerans ARK 17, Streptomyces recifensis ARK 63, Streptomyces tendae ARK 91, and Streptomyces manipurensis ARK 94 were used in this study. All of the isolates could grow in potato broth, rice bran extract, and molasses as alternative media. The highest biomass produced from the molasses growth medium. All five isolates had antifungal activity against F. oxysporum with the inhibition percentage ranging from 41% to 76%, and all of them were detected to have the iaaM gene. Indole-3-acetic acid (IAA) hormone produced by these isolates were ranging from 8.99-15.14 mg L-1, with the phosphate solubilization index of 2.13-2.47. Five rhizosphere Streptomyces formulas with the main carrier of peat could maintain the viability with the population density of 108 CFU g-1 for 8 weeks of storage at room temperature. Two formulas, F17 and F94, were the best formulas to control disease caused by F. oxysporum with disease suppression of 74% in sterile soil and 80-85% in non-sterile soil. Formula F17 and F94 significantly increased soybean growth in sterile and non-sterile soils. Therefore, these formulas could be recommended as biocontrol and plant growth promoters of soybean.